Aksharas, alphasyllabaries, abugidas, alphabets and orthographic depth: Reflections on Rimzhim, Katz and Fowler (2014). Issue 1 (2nd January 2016) - Share, David L.; Daniels, Peter T.
Abstract : We contend that, contrary to Rimzhim, Katz and Fowler (2014), consonants and vowels in the Brahmi-derived scripts are not "on a par", and, therefore, that it is inaccurate to depict these scripts as alphabetic. Furthermore, we consider the popular terminology "alphasyllabic" to be misleading because these scripts are neither alphabetic nor syllabic. We argue on historical grounds that Brahmi-derived scripts (the script family known as Indic) are in a category of their own and merit a unique descriptor such as "abugida". We also consider the authors' concept of orthographic depth to be problematic outside the context of European alphabets because orthographic depth across the full spectrum of the world's writing systems is multi-dimensional rather than uni-dimensional. We suggest that at least 10 dimensions of orthographic depth (or complexity) are needed to capture writing system diversity. Finally, we briefly discuss some educational implications of classification and mis-classification of writing systems.